2014
DOI: 10.1007/s12026-014-8532-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer vaccines in combination with additional treatment modalities

Abstract: Immunotherapy has been investigated in both preclinical studies and clinical trials as a new therapy for prostate cancer. Vaccines, including those that utilize dendritic cells, viruses, or DNA, immunize against prostate-specific antigen and prostatic acid phosphatase. The vaccines have long been studied as monotherapy for the cancer, but increasingly more trials have been initiated in combination with other modalities. These include radiation, chemotherapy, and androgen deprivation therapy. This review descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Currently investigated immunovacines include dendritic cell vaccine with a chimeric protein as a tumor-associated antigen; PSA antigen co-stimulatory molecules delivered in viral vectors; irradiated prostate cancer cell lines; adenovirus/PSA vaccine in men with recurrent cancer after local therapy and with hormone refractory cancer; DNA-based vaccines and adenoviral vector-expressing Herpes virus thymidine kinase, which targets tumor cells and is followed by anti-herpes drug (71). Immune modulators used in studies include cytotoxic T-lymphocyte-associated antigen 4 and CT-011 anti-programmed death receptor-1 for advanced stages of prostate cancer.…”
Section: Prostate Cancer and Inflammationmentioning
confidence: 99%
“…Currently investigated immunovacines include dendritic cell vaccine with a chimeric protein as a tumor-associated antigen; PSA antigen co-stimulatory molecules delivered in viral vectors; irradiated prostate cancer cell lines; adenovirus/PSA vaccine in men with recurrent cancer after local therapy and with hormone refractory cancer; DNA-based vaccines and adenoviral vector-expressing Herpes virus thymidine kinase, which targets tumor cells and is followed by anti-herpes drug (71). Immune modulators used in studies include cytotoxic T-lymphocyte-associated antigen 4 and CT-011 anti-programmed death receptor-1 for advanced stages of prostate cancer.…”
Section: Prostate Cancer and Inflammationmentioning
confidence: 99%
“…For example, Sipuleucel-T is the first immunotherapy approved by the US FDA in 2010 for men with castrate-resistant prostate cancer, 19,20 However, unlike radiation and chemotherapy, immunotherapies are not immediately cytotoxic and can not promptly decrease tumor burden. Thus, therapies to combine immunotherapies with chemotherapy, radiation and androgen deprivation therapy are highly recommended.…”
Section: A Case Study Related To Immune Therapymentioning
confidence: 99%
“…Thus, therapies to combine immunotherapies with chemotherapy, radiation and androgen deprivation therapy are highly recommended. 19 An invention identifies a method that can assist physicians to better select drug treatments and in particular combination drug compositions for individual patients with prostate cancer. The independent claim was drafted as:…”
Section: A Case Study Related To Immune Therapymentioning
confidence: 99%
“…A phase II clinical trial involving men with metastatic CRPC reported that those given Prostvac-VF concurrently with docetaxel had longer progression-free survival than patients given the vaccine alone (3.2 months versus 1.8 months) [90], but this clearly needs to be validated in large prospective trials. On the other hand, a phase III trial that investigated the effects of GVAX plus docetaxel was terminated early following preliminary findings that the combination treatment was associated with shorter survival and had a higher death rate compared to the docetaxel plus prednisone control group [91]. To properly assess the clinical utility of chemoimmunotherapy, it is necessary to consider the optimal timing and scheduling of treatments.…”
Section: A Perspective On the Future Of Immunotherapy For Pcamentioning
confidence: 99%